Technology-Based Referral System In Handling Emergency Catfish Diseases In Primary Services - Porkas Lubis, Muhammad Ishaq (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Catastrophic diseases, such as stroke, heart attack, and severe trauma, require rapid and well-coordinated emergency care to prevent fatal outcomes. Primary healthcare facilities often serve as the first point of contact for these critical cases, making an efficient referral system essential. However, conventional referral systems frequently face challenges, including delays, miscommunication, and a lack of real-time patient data, which can negatively impact patient outcomes. The integration of technology-based referral systems has the potential to enhance emergency response and streamline the transfer of critically ill patients to higher-level healthcare facilities.This study aims to analyze the effectiveness of technology-based referral systems in improving the management of catastrophic diseases in primary healthcare settings and their impact on patient outcomes.A literature review and data analysis were conducted to evaluate the role of digital referral platforms, telemedicine, and real-time patient monitoring systems in emergency referrals. Data were collected from case studies, research articles, and reports related to technology-driven emergency response in primary healthcare services.The findings indicate that technology-based referral systems significantly improve response time, communication between healthcare providers, and the overall efficiency of patient transfers. Digital platforms facilitate faster decision-making, reduce administrative burdens, and provide real-time access to critical patient information. Moreover, telemedicine consultations enable primary healthcare providers to receive immediate guidance from specialists, leading to more accurate diagnoses and pre-transfer stabilization of patients. As a result, patients with catastrophic diseases experience better survival rates, reduced complications, and improved continuity of care.The integration of technology in referral systems is a crucial advancement in emergency healthcare, particularly for catastrophic diseases requiring urgent intervention. To maximize its benefits, standardized protocols, interoperability between digital platforms, and adequate training for healthcare personnel must be implemented. Policymakers and healthcare institutions should prioritize the adoption of digital referral systems to enhance emergency medical services and improve patient outcomes in primary healthcare settings.